2020
DOI: 10.1039/d0cy00733a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic self-etherification of 5-hydroxymethylfurfural to 5,5′(oxy-bis(methylene))bis-2-furfural over zeolite catalysts: effect of pore structure and acidity

Abstract: Understanding the role of pore structure and acidity of zeolite catalyst in the self-etherification of 5-hydroxymethylfurfural to 5,5′(oxy-bis(methylene))bis-2-furfural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Because the dimerization of C 6 H 8 O 4 could form a compound with the formula of C 12 H 16 O 8 , we proposed that the compound C 12 H 16 O 8 (18.23 min) should be formed by the aldol condensation of DHH or 5,6-dihydroxy-2-oxohex-3-enal, whereas the compounds C 12 H 14 O 7 (20.23 min) and C 12 H 12 O 6 (16.71 min) were formed from C 12 H 16 O 8 (18.23 min) by losing 1 and 2 moles of water, respectively. The compound C 12 H 10 O 5 should be a dimer of HMF formed by etherification . In contrast, the H/O atom ratios of C 10 H 18 O 6 (15.31 min), C 8 H 18 O 3 (20.76 min), C 10 H 12 O 4 (22.58 min), and C 12 H 26 O 4 (26.54 min) were not equal to 2, indicating that butanediol may participate in the formation of these compounds .…”
Section: Resultsmentioning
confidence: 94%
“…Because the dimerization of C 6 H 8 O 4 could form a compound with the formula of C 12 H 16 O 8 , we proposed that the compound C 12 H 16 O 8 (18.23 min) should be formed by the aldol condensation of DHH or 5,6-dihydroxy-2-oxohex-3-enal, whereas the compounds C 12 H 14 O 7 (20.23 min) and C 12 H 12 O 6 (16.71 min) were formed from C 12 H 16 O 8 (18.23 min) by losing 1 and 2 moles of water, respectively. The compound C 12 H 10 O 5 should be a dimer of HMF formed by etherification . In contrast, the H/O atom ratios of C 10 H 18 O 6 (15.31 min), C 8 H 18 O 3 (20.76 min), C 10 H 12 O 4 (22.58 min), and C 12 H 26 O 4 (26.54 min) were not equal to 2, indicating that butanediol may participate in the formation of these compounds .…”
Section: Resultsmentioning
confidence: 94%
“…The choice of etherification agent is usually determined by the targeted product specifications. For example, the self-etherification of 5-HMF in the presence of a solid Brønsted acid, like H-ZSM-5, yields 5,5′-OBMF (Figure a) . This compound is useful as a precursor for imine-based polymers as well as an antiviral agent against hepatitis.…”
Section: Protection Strategiesmentioning
confidence: 99%
“…For example, the self-etherification of 5-HMF in the presence of a solid Brønsted acid, like H-ZSM-5, yields 5,5′-OBMF (Figure 7a). 58 This compound is useful as a precursor for imine-based polymers as well as an antiviral agent against hepatitis. Yields up to 90% have been reported, and the conversion correlates with the concentration of Brønsted acid sites.…”
Section: ■ Protection Strategiesmentioning
confidence: 99%
“…Although the introduction of mesoporous into the microporous zeolites by dual template method or post treatment method could improve the catalytic performance to a certain extent, the use of expensive templating agent and the severe mass loss of zeolites in post treatment process brought many questions such as catalyst economy, exhaust emission, and waste water treatment [5b,9] . Moreover, our previous work demonstrated that the strong acidity of zeolites could lead to the occurrence of side reactions (containing ring‐opening, hydrogenolysis, polymerization, etc) [8c,9b] . Amorphous silica‐aluminas (ASA), an exceptional type of porous materials, were also extensively used as solid acid catalysts and supports in the petrochemical industry [10] .…”
Section: Introductionmentioning
confidence: 99%